Constraints faced by the Tribal Youth in Vocational Preference - Sundaran, Dhanush; Murugan, P.P (Journal of Extension Education, 2019)
Tribes are considered as primitive people and they are cut-off from the social and political structures of development. The present study identified the constraints faced by the tribal youth in The Nilgiris district, Tamil Nadu. Data were collected from the tribal youth through a structured interview schedule developed for the study. A majority of the tribal youth reported that insufficient credit facilities was the major constraint faced by them. Other major constraints faced by the tribal youth were lack of periodical training, land alienation and job insecurity.